A Sustainable Mine Water Treatment Initiative to Provide Potable Water for a South African City ù A Public-Private Partnership - W Mey; A M. van Niekerk (The Australasian Institute of Mining and Metallurgy, 2006)
Coal mining has an impact on the water management of the water scarce Upper Olifants River Catchment. A prefeasibility study was carried out by Anglo Coal and Ingwe Collieries Limited to establish the water supply and demand in the catchment. A geohydrological model was used for the coalfields to determine the stored water and excess water available. Two distinct collective and treatment systems were proposed for the Witbank and Middelburg municipalities to treat excess water from the Anglo Coal and Ingwe Collieries Limited. The Emalahleni Water Reclamation Project for Witbank was initiated first. Water management and treatment experience gained at Anglo Coal was the cornerstone to develop the collection, treatment and distribution system. A full enquiry was issued to Keyplan, Veolia, Bateman Africa and IST Technik to construct, commission, operate and maintain a 20 ML/day desalination plant to treat acidic, saline mine waters to a South African National Standard (SANS) 0241 Class 0 potable water. After the technical and financial adjudication, Keyplan were awarded the contract. An integrated regulatory process was adopted through consultation with all the relevant regional and head office staff of the Department of Minerals and Energy, Department of Water Affairs and Forestry and the Mpumalanga Department of Land Affairs via an authorityÆs steering committee. A rock engineering evaluation was done to select both the plant and waste disposal sites as all possible sites are undermined. Various contracts are required with the individual mines for water supply, the Emalahleni Local Municipality for the delivery of potable water and for the disposal of wastes.